A Tale of Two Isomers: Enhanced Antiaromaticity/Diradical Character versus Deleterious Ring‐Opening of Benzofuran‐fused s‐Indacenes and Dicyclopenta[b, g]naphthalenes. Issue 41 (9th September 2021) - Barker, Joshua E.; Price, Tavis W.; Karas, Lucas J.; Kishi, Ryohei; MacMillan, Samantha N.; Zakharov, Lev N.; Gómez‐García, Carlos J.; Wu, Judy I.; Nakano, Masayoshi; Haley, Michael M.
Abstract: We examine the effects of fusing two benzofurans to s ‐indacene (indacenodibenzofurans, IDBFs) and dicyclopenta[ b, g ]naphthalene (indenoindenodibenzofurans, IIDBFs) to control the strong antiaromaticity and diradical character of these core units. Synthesis via 3‐functionalized benzofuran yields syn ‐IDBF and syn ‐IIDBF. syn ‐IDBF possesses a high degree of paratropicity, exceeding that of the parent hydrocarbon, which in turn results in strong diradical character for syn ‐IIDBF. In the case of the anti ‐isomers, synthesized via 2‐substituted benzofurans, these effects are decreased; however, both derivatives undergo an unexpected ring‐opening reaction during the final dearomatization step. All the results are compared to the benzothiophene‐fused analogues and show that the increased electronegativity of oxygen in the syn ‐fused derivatives leads to enhancement of the antiaromatic core causing greater paratropicity. For syn ‐IIDBF increased diradical character results from rearomati‐zation of the core naphthalene unit in order to relieve this paratropicity. Abstract : Fusion of benzofuran to either s ‐indacene or dicyclopenta[ b, g ]naphthalene results in two dramatically different outcomes depending upon heterocycle orientation. Whereas the "anti" isomers are unstable and hydrolyze readily to ring‐opened products, the "syn" isomers are quite stable and afford molecules that either possess a high degree of antiaromaticity or exhibit pronounced diradical character.